Ab initio phasing by molecular averaging in real space with new criteria: application to structure determination of a betanodavirus. Issue 7 (5th July 2016) - Yoshimura, Masato; Chen, Nai-Chi; Guan, Hong-Hsiang; Chuankhayan, Phimonphan; Lin, Chien-Chih; Nakagawa, Atsushi; Chen, Chun-Jung
Abstract : A two‐step process of phase determination in the X‐ray structural analysis of the coat protein of a betanodavirus is described. A new indicator, the free fraction, for molecular averaging in real space is introduced to effectively evaluate the phasing power in order to enhance the success of determining new structures. Abstract : Molecular averaging, including noncrystallographic symmetry (NCS) averaging, is a powerful method for ab initio phase determination and phase improvement. Applications of the cross‐crystal averaging (CCA) method have been shown to be effective for phase improvement after initial phasing by molecular replacement, isomorphous replacement, anomalous dispersion or combinations of these methods. Here, a two‐step process for phase determination in the X‐ray structural analysis of a new coat protein from a betanodavirus, Grouper nervous necrosis virus, is described in detail. The first step is ab initio structure determination of the T = 3 icosahedral virus‐like particle using NCS averaging (NCSA). The second step involves structure determination of the protrusion domain of the viral molecule using cross‐crystal averaging. In this method, molecular averaging and solvent flattening constrain the electron density in real space. To quantify these constraints, a new, simple and general indicator, free fraction (ff), is introduced, where ff is defined as the ratio of the volume of the electron density that is freely changed to the total volume of the crystal unit cell. This indicator is useful and effective to evaluate the strengths of both NCSA and CCA. Under the condition that a mask (envelope) covers the target molecule well, an ff value of less than 0.1, as a new rule of thumb, gives sufficient phasing power for the successful construction of new structures.